HUBUNGAN PERSEPSI SISWA TENTANG PROSES PEMBELAJARAN DENGAN HASIL BELAJAR GAMBAR TEKNIK SISWA KELAS X TGB SMK N 2 PAYAKUMBUH - 2091-2094, Giva Maulani (Universitas Negeri Padang, 2018)
Abstract—. This research to reveal the relationship of students' perceptions about the learning process with the learning outcomes of Technical Drawing Course of students of Class X TGB SMKN 2 Payakumbuh. The type of this research is a correlational descriptive research. The samples were 49 students taken by using total sampling technique. Data analysis techniques used are: 1) Descriptive analysis, 2) Analysis requirements test, consisting of normality test and linearity test, and 3) Test of Hypothesis. The result of this study showed that there is a significant relationship between students' perceptions of the learning process with the learning outcomes of Technical Drawing Courses of students of Class X TGB SMKN 2 Payakumbuh, with 95% confidence level. This can be seen from the correlation coefficient value of 0.552, means that the relationship lies in moderate category.Keywords: Student Perception, Learning Process, Learning Result